Las revistas “Militancia Peronista para la Liberación” y “De Frente con las bases peronistas”: una propuesta “alternativa” para la identidad política del peronismo revolucionario, 1973-1974 - Mariela Stavale (Nuevo mundo - Mundos Nuevos, 2020)
This work searches the political identity transformation of two political-cultural magazines which have not been analysed until now: “Peronist Militancy for Liberation” (Militancia Peronista para la Liberación - MPL) and its continuation in “Head On, together with Peronist Militant Core” (De Frente, con las bases peronistas - DF) that were published between June 1973 and July 1974. Both magazines arise within the particular context of the third peronist government, after years of political proscription and pursue to be constituted as a wide expression organ for a heterogeneous group: The Revolutionary Peronist Tendency. This doctoral thesis seeks to problematize the publishing and militant experience of the political group which arose around MPL and DF, in order to account for the transformation processes within its political identity which constituted at the same time, a proposal for the whole revolutionary peronism.The experiences that join both magazines and the interest to identify change elements and continuities led us to rank two relevant dimensions. On one hand, a diachronic dimension, by seeking to weave bridges with the previous period, that is to say, with the junction process between political-cultural traditions and the conformation of new political identities, which far from crystallized, they kept on redefining their limits. On the other hand, the synchronic dimension made us focused in the period in which MPL and then DF were published, i.e. 1973 and 1974, by analysing the third peronist government experience and the political-ideological discussions that, within that moment, took shape in the revolutionary peronist core.